2006
DOI: 10.1128/aac.50.3.943-948.2006
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone Resistance in Invasive Streptococcus pyogenes Isolates Due to Spontaneous Mutation and Horizontal Gene Transfer

Abstract: Fluoroquinolone resistance in Streptococcus pyogenes has been described only anecdotally. In this study we describe two invasive ciprofloxacin-resistant S. pyogenes isolates (ciprofloxacin MICs, 8 mg/liter), one of which shows evidence of interspecies recombination. The quinolone resistance-determining regions of gyrA and parC were sequenced. In both isolates, there was no evidence for an efflux pump and no mutation in gyrA. Both isolates had an S79F mutation in parC that is known to confer fluoroquinolone res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 22 publications
2
23
0
1
Order By: Relevance
“…Only one strain had a single mutation in GyrB without mutations in GyrA, ParC, or ParE. The resistance mutations in GyrA and ParC in our strains occurred at the expected hot spots (GyrA-S81Y; ParC-S79Y), which are generally similar to those reported by Escudero et al (13) and those in other Gram-positive bacteria, such as S. aureus, S. pneumoniae, S. pyogenes, and E. faecium (18,(24)(25)(26)(27). It has already been demonstrated that QRDR alterations in GyrB and ParE are associated with fl uoroquinolone resistance in Gram-positive bacteria such as S. aureus, S. pneumoniae, and E. faecium (25,27,28), but this has not been reported in S. suis.…”
Section: Discussionsupporting
confidence: 75%
“…Only one strain had a single mutation in GyrB without mutations in GyrA, ParC, or ParE. The resistance mutations in GyrA and ParC in our strains occurred at the expected hot spots (GyrA-S81Y; ParC-S79Y), which are generally similar to those reported by Escudero et al (13) and those in other Gram-positive bacteria, such as S. aureus, S. pneumoniae, S. pyogenes, and E. faecium (18,(24)(25)(26)(27). It has already been demonstrated that QRDR alterations in GyrB and ParE are associated with fl uoroquinolone resistance in Gram-positive bacteria such as S. aureus, S. pneumoniae, and E. faecium (25,27,28), but this has not been reported in S. suis.…”
Section: Discussionsupporting
confidence: 75%
“…Prior to the introduction of gatifloxacin and moxifloxacin, all isolates with mutations observed in the QRDRs of S. pneumoniae had mutations in the parC gene (3,10). Since the introduction of gatifloxacin and moxifloxacin, the number of isolates with parC mutations has remained stable, but there has been an increase in the proportion of isolates with gyrA-only mutations (12,13,24).…”
Section: Discussionmentioning
confidence: 99%
“…High-level resistance results from additional point mutations in the DNA gyrase (gyrA and gyrB) genes (521). These point mutations may be acquired by spontaneous mutation within the QRDR or via horizontal gene transfer (527). The subsequent clonal expansion of resistant strains has contributed to rapid increases in the prevalences of fluoroquinolone-resistant GAS isolates in recent years (521).…”
Section: Tetracycline Resistancementioning
confidence: 99%